The Effect Of Using Mathematics Laboratory On Developing Geometrical Thought Skills Among Eighth Grade Students (A semi-Empirical Study In The City Of Lattakia) - نصور رغداء (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study aimed to know the effect of using Mathematics Laboratory on mathematics education to develop Geometrical Thought choices among Eighth Grade Students. To achieve this goal, the researcher built the educational material based on Mathematics Laboratory and presented it to a group of arbitrators and then tried it before the final application, The Geometrical Thought test was applied to pupils after completing the teaching of the educational subject ,and the study sample reached (60 ) pupils from the Eighth basic class in the city of lattakia divided into two experimental and control groups. The results of the study showed a difference between the mean scores of the experimental and control groups in the post application of the Geometrical Thought test, and the superiority of the students of the experimental group may be attributed to the use of class activities in teaching unit Geometrical on them, whereas, teaching in this way has contributed to developing Geometrical Thought skills among the students of the experimental group better compared to the usual method .The study also showed a difference between the mean scores of the experimental group in the pre and post applications for the Geometrical Thought Skills test in favor of the post application,The researcher suggested relying on the Mathematics Laboratory in teaching mathematics and all the academic stages due to its importance in increasing and developing Geometrical Thought skills for students and thus achieving the goals of mathematics curricula.